Evolution of seed mass associated with mating systems in multiple plant families. (26th October 2021) - Tateyama, Hirofumi; Chimura, Kaori; Tsuchimatsu, Takashi
Abstract: In flowering plants, the evolution of self‐fertilization (selfing) from obligate outcrossing is regarded as one of the most prevalent evolutionary transitions. The evolution of selfing is often accompanied by various changes in genomic, physiological and morphological properties. In particular, a set of reproductive traits observed typically in selfing species is called the "selfing syndrome". A mathematical model based on the kinship theory of genetic imprinting predicted that seed mass should become smaller in selfing species compared with outcrossing congeners, as a consequence of the reduced conflict between maternally and paternally derived alleles in selfing plants. Here, we test this prediction by examining the association between mating system and seed mass across a wide range of taxa (642 species), considering potential confounding factors: phylogenetic relationships and growth form. We focused on three plant families—Solanaceae, Brassicaceae and Asteraceae—where information on mating systems is abundant, and the analysis was performed for each family separately. When phylogenetic relationships were controlled, we consistently observed that selfers (represented by self‐compatible species) tended to have a smaller seed mass compared with outcrossers (represented by self‐incompatible species) in these families. In summary, our analysis suggests that small seeds should also be considered a hallmark of the selfing syndrome, although we note that mating systems have relatively small effects on seed mass variation. Abstract : Association between seed mass and mating systems (self‐incompatible [SI] and self‐compatible [SC]) in three plant families.